The Influence of Telmisartan on the Expression of BMP-7 in Rat Kidneys Induced by 8% NaCl - Khairil Pahmi; Lale Syifaun Nufus; Sriama Muliani (JIKF, 2022)
Excessive salt intake is one of the factors of high blood pressure leading to kidney disease while telmisartan is one of the antihypertensive drugs used in therapy. Telmisartan not only blocks the angiotensin receptor, which leads to a reduction in blood pressure, but also activates the peroxisome proliferator-activated receptor gamma (PPAR-γ), inhibits the expression of transforming growth factor beta-1 (TGFβ-1) and increases bone morphogenetic protein-7 (BMP-7). This experiment examines whether telmisartan increases the expression of BMP-7 in excess NaCl-induced Wistar rats. For this study, 25 male Wistars aged 2.5 to 3 months and rats weighing 100 to 150 g were used.They were grouped into 5, each consists of 5 rats. Group I (G I) as the first negative control received neither NaCl nor telmisartan. G II as the second negative control received NaCl but no telmisartan. G III, IV and V received NaCl and telmisartan 3, 6 and 12 mg/kg body weight. Treatments were given every day for 8 weeks.On day 56, all rats were sacrificed by neck dislocation and operated on to remove the kidney. BMP-7 expression was measured by immunohistochemical technique. Data were expressed as mean ± standard error. They were analyzed by parametric (ANOVA) or nonparametric (Kruskal-Wallis) testing. A value of p ≤ 0.05 was considered statistically significant. The results showed that the expression of the intraglomerular and extraglomerular protein BMP-7 was higher in the telmisartan-treated group of Wistar rats than in the negative control group (pand<0.05). In summary, intraglomerular and extraglomerular BMP-7 protein expression was higher in male Wistar rats treated with telmisartan and induced with 8% sodium chloride than in negative control group members.